The Urgency of Implementing an Appropriate Legislative Election System in Democracy Development in Indonesia - Filshella Goldwen (CV. Rayyan Dwi Bharata, 2023)
The Urgency of Implementing the Legislative General Election System Open and closed proportional election systems (elections) are two legislative election systems that differ in the way votes are counted and the allocation of seats in parliament. The two systems shocked the public because of plans to re-implement a closed proportional election system, which was marked by a lawsuit for judicial review of the Election Law to the Constitutional Court (MK) with case number 114/PUU-XX/2022. In this research, a normative research method was used with a comparative approach to the two systems based on several criteria, including effectiveness in representing various political interests, political stability, and people's participation in politics. The purpose of this study is to identify and examine the proper application of the legislative election system in the development of democracy in Indonesia. The results of this study indicate that an open proportional electoral system in the election of candidates for legislative members tends to be more appropriate in the development of democracy in Indonesia and is more effective in representing diverse political interests and strengthening political parties as political institutions. With this system, the development of democracy in Indonesia will be even better with well-run elections that uphold people's sovereignty.